Penyuluhan Kesehatan Reproduksi dan Pelatihan Senam Dismenore Santriwati Pondok Gontor Putri 2 Mantingan, Ngawi - Nurul Marfu'ah; Amilia Yuni Damayanti; Indah Tri Lestari (LP3M STAI Darussalam Krempyang Nganjuk, 2021)
Lack of knowledge about women's reproduction health causes santriwati to experience several problems, such as menstrual pain (dysmenorrhea). The purpose of this activity is a) to increase knowledge about women's reproduction health, b) to help respondents overcome dysmenorrhea by doing exercise. Respondents used were 342 santriwati. The method used is counseling about women's reproduction health. Before the counseling, the respondents' knowledge level about reproduction health consisted of Very Good (84.50%) and Good (15.50%). After the counseling, 100% of the respondents knew Very Good about reproduction health knowledge, especially material about menstruation, pregnancy, postpartum, breastfeeding, infertility, IVF and cloning. While the dysmenorrhea exercise training carried out showed the results that before the training, the level of knowledge of the respondents regarding the existence of dysmenorrhea exercise consisted of Good (2.34%), Less Good (26.31%) and Very Good (71.35%) but they could not practice it. After training, 99.71% of respondents know and can practice dysmenorrhea exercise Very Good.